Effect of Hepatitis C virus infection on selected laboratory values in pregnant women with Human Immunodeficiency virus infection (2016)
Background and Objectives: Both hepatitis C and Human Immunodeficiency viruses affect laboratory indices. The objective of this study was to describe the impact of both viruses on laboratory indices among 1,821 HIV-positive pregnant women. Methods: This was a cross-sectional retrospective study at the University College Hospital, Ibadan Results: Twenty-six (1.7%) women were HCV positive, 139 (8.8%) were HBsAg positive and 1, 407 (89.3%) were negative for both viruses. Three patients (0.19%) were positive for both viruses. These patients, the HBsAg positive women and 246 with no result for either virus were excluded from analysis. The HCV positive women had lower hematocrit (27.3% + 4.5 vs. 28.4% + 4.6, p=0.29), lower WBC (5, 200 vs. 5, 500 cells/ml, p =0.766) but higher platelet count (209, 000 vs. 199, 000 cells / ml, p = 0.019). The coinfected group had higher CD4 (380 vs. 326 cells/ml, p = 0.319), higher urea (16.0vs.ll.0mg/ml, p =0.013) but comparable ALT (16.0 vs.15.0 iu/ml, p = 0.95), log viral load (4.08+1.22 vs. 4.08+1.11, p=0.97) and creatinine levels (0.6vs.0.6, p=0.329). Only the difference in urea level was statistically significant. Conclusion: While values were comparable between both groups, the synergistic effect of both viruses makes it necessary for health-care providers to closely monitor patients.